Designing a Teaching Framework With a Focus on Forming Multiple-nets to Map Student Creativity Patterns - Qadeer, Altaf (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
Abstract To inspire students’ creativity for making science fair models and other science projects. A framework is provided with links to deep learning and multiple-nets. Making connections between ideas, subjects and material objects is mapped in a framework to develop some creativity patterns. Teachers are provided with a rubric to possibly apply this framework in the classrooms. The pathway of multiple-nets can be applied effectively in a vast range of activities and this approach is also supported by some theoretical grounds. Further studies will be needed to analyze and expand this approach for specific parameters at various levels.